Personogenesis Through Imitating Human Behavior in a Humanoid Robot “Alter3” - Masumori, Atsushi; Maruyama, Norihiro; Ikegami, Takashi (Frontiers in Robotics and AI, 2021)
A new imitation humanoid robot called Alter3 is presented. Alter3 mimics human poses with its camera eyes and an internal build-in simulator, pre-simulating his own future actions. Alter3also stores action sequences in the memory layer. The purpose of this paper is to study how this mimicry works and how to quantify it using transfer entropy, UMAP compression, and other techniques. This provides a new approach to study guided self-organization of cognitive robots.